HYPOCHOLESTEROLAEMIC EFFECT OF LEAF PROTEIN CONCENTRATE (LPC) ON BLOOD CHOLESTEROL OF RATS AND POULTRY (Biological Sciences - PJSIR, 2002)
Leaf protein concentrate (LPC) was extracted from barseem leaves and incorporated in the diet replacing  casein  in case of  rats and fishmeal in poultry. A series of experiments were cond ucted on rats and poultry to determine the hypocholesterolaemic effect of LPC on the blood cholesterol of rats  and poultry.  Results  indicated  that incorporation  of  LPC decreased cholesterol level of blood in rats and poultry. Decrease in phospholipids has also been noticed with  the  increase in concentration of LPC. Decrease in cholesterol content in  eggs laid by hens fed on diet containing LPC has also  been  observed.